A business plan for HomeyCafe, a restaurant that specialises in bringing global stews and soups to the local market - Thew, Allan Yeng Hui (2023)
This business plan outlines the strategic and operational blueprint for a restaurant business that addresses the challenges associated with current and emerging F&B trends/disruptions caused by new technologies and social changes. It does this by Incorporating modern technology and offering a unique menu concept. Its strategies combine Lean management elements from an operations and customer perspective to design a sustainable business plan that drives revenue generation, cost savings, address resource issues and builds capabilities to serve a wide scope of customers with its unique selling proposition.